2001
DOI: 10.1257/aer.91.5.1239
|View full text |Cite
|
Sign up to set email alerts
|

Does Money Illusion Matter?

Abstract: Money illusion means that people behave differently when the same objective situation is represented in nominal or in real terms. To examine the behavioral impact of money illusion we studied the adjustment process of nominal prices after a fully anticipated negative nominal shock in an experimental setting with strategic complementarity. We show that seemingly innocuous differences in payoff presentation cause large behavioral differences. In particular, if the payoff information is presented to subjects in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
174
0
14

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(202 citation statements)
references
References 30 publications
14
174
0
14
Order By: Relevance
“…However, in contrast to Miller et al (1989), while the situations are statistically equivalent a priori, the actual probability of success may depend on others' choice in some scenarios. These findings on likelihood are similar to the findings on money illusion -a tendency to think in terms of nominal rather than real monetary values -by Fehr and Tyran (2001). Fehr and Tyran (2001) show that money illusion could be quite substantial and long lasting, not because of individual mistakes, but because some people behave differently in anticipation of money illusion by others.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…However, in contrast to Miller et al (1989), while the situations are statistically equivalent a priori, the actual probability of success may depend on others' choice in some scenarios. These findings on likelihood are similar to the findings on money illusion -a tendency to think in terms of nominal rather than real monetary values -by Fehr and Tyran (2001). Fehr and Tyran (2001) show that money illusion could be quite substantial and long lasting, not because of individual mistakes, but because some people behave differently in anticipation of money illusion by others.…”
Section: Introductionsupporting
confidence: 85%
“…These findings on likelihood are similar to the findings on money illusion -a tendency to think in terms of nominal rather than real monetary values -by Fehr and Tyran (2001). Fehr and Tyran (2001) show that money illusion could be quite substantial and long lasting, not because of individual mistakes, but because some people behave differently in anticipation of money illusion by others. These findings are also reminiscent of the findings by Shafir, Diamond, and Tversky (1997), who show that although most people can distinguish between nominal and real monetary values, they still tend to prefer a higher nominal value.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…On the one hand, several welldesigned psychological experiments at the individual level show a convincing bias towards nominal rather than real magnitudes, which according to these findings results in considerable inertia (see Shafir et al (1997);Fehr and Tyran (1997)). On the other hand, recent experience also appears to provide clear-cut evidence for the existence of money illusion at the individual and aggregate levels.…”
Section: Money Illusion: Neglected In Research and Policymentioning
confidence: 88%
“…Using a variety of empirical approaches, researchers have found strong indications of money illusion. Examples are Shafir et al (1997) using stated preference data, Fehr and Tyran (2001) using laboratory experiments, and Kooreman et al (2004) using a quasiexperimental approach. Kooreman et al (2004) found that after the introduction of the euro people donated more in real terms to a charity than they did before.…”
Section: Framing Effectsmentioning
confidence: 99%